(untitled) (CIPEEX, 2023)
The dental crack consists of an incomplete fracture, which involves enamel and dentin. This crack breaks the continuity of the dentin with unknown depth and direction, potentially progressing to a communication with the pulp and/or periodontal ligament, leading to a complete fracture. Thus, it is important to know the best treatment both to alleviate the painful symptoms and to prevent the progression of the crack. The objective of this study will be to evaluate the influence of crack preparation and cusp coverage on the stresses and deformations of molars using the three-dimensional finite element method. Four models will be created based on the combination of two study factors: 1- crack preparation: with and without preparation; 2- cusp covering: with and without covering. In a three-dimensional graphic design program (SolidWorks 2018), a prototype of a human lower molar will be constructed and restored using the 4 approaches. The four models will be exported to specific finite element analysis software (Ansys Workbench) and mechanical properties, meshing, boundary conditions, and loading will be added. An oblique static occlusal load (30º) of 131.9 N will be applied to the grinding cusp of the tooth, simulating the displacement to perform the chewing function. The analysis will be both quantitative and qualitative with the variables of maximum principal stress (tension), maximum shear stress, and maximum displacement for both the reconstructions and the dental remnant. It is expected that, at the end of the conducted study, the approach associated with the highest stress value will be the one without crack dissection and with cusp coverage.